Ischemic Colitis after Weight-Loss Medication - Dan Comay; Jennifer Ramsay; E Jan Irvine (Canadian Journal of Gastroenterology)
BACKGROUND: Previous weight-loss medications have received cautious support due to their association with pulmonary hypertension and valvular heart disease. However, newer drugs are increasingly being recommended as potentially safer and more efficacious. We report a case of ischemic colitis possibly linked to the use of a weight-loss drug, and review the literature to highlight an important latent consequence of these medications.